Case studies in star formation a molecular astronomy perspective - MacKay, Duncan (Cambridge University Press, 2023)
This volume offers an overview of our current observational and theoretical understanding in the molecular astronomy of star formation. It provides copious observational detail and theoretical analysis through the lens of large-scale surveys and individual sources, raising major research questions for graduate students and early researchers.